COVID‐19 and dental workers: The Italian Society of Periodontology and Implantology (SIdP) survey. (8th October 2021) - Nicola, Discepoli; Raspini, Mario; Landi, Luca; Sforza, Nicola; Crea, Alessandro; Cavalcanti, Raffaele; Cairo, Francesco
Abstract: Objectives: To evaluate the proportion of COVID‐19 infections among a population of Italian Dental workers across different geographical area of Italy and to analyze the impact of both the preventive measures/strategies adopted and the psychological influences. Subjects and Methods: The current cross‐sectional survey was administered with a web‐based form. To be eligible for the study, participants had to be 18 years and being dentists or dental hygienists members of the Italian Society of Periodontology and Implantology (SIdP). A 23‐item questionnaire concerning positiveness to COVID‐19, clinical strategies and psychological attitude within the pandemic was administered. Sub‐group analysis was conducted according to geographical macro‐area. Results: A total of 790 dentists and dental hygienists were included. A total of 4.7% participants developed a positive diagnosis to COVID‐19. The Northwest of Italy experienced almost double of COVID‐19‐positive participants ( p < 0.05). Preoperatory mouthwashes together with natural air change/ventilation were the most frequent approaches used to prevent COVID‐19 outbreak. Positive and proactive attitudes were predominant among participants. Only a reduced proportion feels some concerns for the future. Conclusions: Prevalence of positive COVID‐19 among dental workers in Italy was double in Northwest area in comparison with the whole country proportion. Preventive strategies comprise mainly ultrasound reduction and preoperative mouthwashes.